PURCHASE DECISIONS OF HERBAL SOAP LOCAL PRODUCT BASED ON MARKETING MIX - Leevisitpattana, Passakorn; Srisopa, Anong (Life Sciences and Environment Journal, 2020)
The objective of this research is to study the consumer behavior on herbal soap local products, and to study the purchase intension towards the herbal soaps based on marketing mix. The investigation was carried out on 384 consumers from municipality area, Phitsanulok province. The results showed that the main reason for herbal soap purchasing of the people who had ever used these soaps was from natural ingredients. The main reason for those who had never used these soaps was the quality. The purchase decisions of the group who had ever used the herbal soap products were having a reasonable price, showing ingredient information, being a solid bar, smelling herbal or fruity scents, cleansing without getting dry skin. The four marketing mixs affecting the purchase decision on herbal soap products were 1) product issues i.e. having clear property labels 2) price issues i.e. displaying price tags 3) distribution marketing channel issues i.e. having additional information access channels 4) marketing promotion issues i.e. supporting from government agencies for credibility and accurate information. Attitudes and purchase decisions on the herbal soap products after receiving product information from research finding (case study of marigold soap) increased for 50.8 %.